Nanotechnologies and Some of their Uses in Environmental Treatments - hadi , Sujjad Hassan; Saidi , Ekram Sabah Sahib Al; Al-Taei , Noor Haider; Abbas , Karima F. (American Journal of Biology and Natural Sciences, 2025)
This review will introduce the basic concept of Nanotechnology, design at the nanoscale, and its processing at the atomic, molecular, and macromolecular scales. It will also explore its uses to solve the global food and energy crises. Although current products represent relatively modest improvements compared to conventional technologies, the future potential of nanotechnology is enormous. Nanotechnology represents the next generation of industrial development that is reshaping markets, research laboratories, and everyday life. Understanding what nanotechnology is and its importance is essential to charting a clear path to the future. It will be used in many fields, including electrical, magnetic, optoelectronic, biological, pharmaceutical, cosmetic, energy, environmental, catalysis, and materials applications. Nanomaterials promote sustainable development, as do their physical and chemical properties and significant contributions to the economy. We will also learn about some nanoscale resources. The role of nanotechnology in environmental treatments is highlighted, as it helps develop innovative cleaning methods and improves the detection and sensing of pollutants.